Effectiveness of a Guided Experimental Method for Increasing Learning Interest in Group B Children at Pertiwi Tluwuk Kindergarten - Febriyanti, Rahma Jihan; Mukminin, Amirul (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2025)
Interest in learning in early childhood classrooms can decline when instruction relies on passive routines and limited hands-on activity. This study examined whether a guided experimental activity could increase learning interest among Group B kindergarten children (5–6 years) at Pertiwi Tluwuk Kindergarten. Using a non-equivalent control-group quasi-experimental design (N = 45; experimental n = 22, control n = 23), the experimental group participated in a low-cost science activity (“bubble fizzy”), while the control group received conventional instruction. Learning interest was measured before and after the intervention through a structured oral assessment administered consistently across groups. Post-test scores were substantially higher in the experimental group (M = 19.45, SD = 2.92) than in the control group (M = 9.96, SD = 3.32), with a mean difference of 9.50 points, 95% CI [7.61, 11.38]. An independent-samples t test showed a significant group difference, t(43) = 10.16, p < .001, with a very large effect size (Hedges’ g = 2.97). The study contributes to the global early childhood literature by showing that short, guided, hands-on experiments can strengthen learning interest in resource-constrained kindergarten settings. Practically, the findings imply that teachers can use brief inquiry-based activities that combine child agency, immediate feedback, and observable cause-effect sequences to increase classroom engagement. However, interpretation remains limited by non-random class assignment, single-site implementation, and reliance on one assessment format. Future studies should use larger multi-site samples, baseline-adjusted analyses, and multimethod measures to test the durability and transferability of the effect across diverse pedagogical, cultural, and institutional contexts.